Manajemen Perawatan Menggunakan Metode RCM Pada Mesin Produksi Kertas - Hery Hamdi Azwir; Arri Ismail Wicaksono; Hirawati Oemar (Jurnal Optimasi Sistem Industri, 2020)
One of the leading manufacturers in packaging paper in Indonesia has six production machines. To keep the production machine always in the best condition, then the role of maintenance is significant. One of the production machines, namely paper production machine 2 (PM2), has experienced increasing the number of breakdowns significantly, resulting in increased downtimes. Sudden failure causes a lengthy repair time and results in considerable production loss. The corrective maintenance method that is running at this time still not effectively reduce downtime. To minimize the number of downtimes, preventive maintenance is needed, and therefore the Reliability Centered Maintenance (RCM) method is selected. Besides applying quantitative analysis such as Mean Time To Repair (MTTR), Mean Time To Failure (MTTF), reliability, and preventive cost calculations. This method also conducts qualitative analysis such as Functional Block Diagrams (FBD), critical engine analysis, Fault Tree Analysis (FTA), and Failure and Mode Effect Analysis (FMEA). After implementing the preventive maintenance, there is an increase in reliability in the sub-system of the press section of the paper production machine 2 from only 43% to 56%, while the repair cost has been reduced by Rp 393,258,670 from Rp 5,724,825,736 to Rp 5,331,567,066 each time replacement of components in the press section. This decrease in costs will contribute to the profits earned by the company because it saves maintenance costs.